2022
DOI: 10.3389/fimmu.2022.860070
|View full text |Cite
|
Sign up to set email alerts
|

Neuroinflammation, Microglia and Implications for Retinal Ganglion Cell Survival and Axon Regeneration in Traumatic Optic Neuropathy

Abstract: Traumatic optic neuropathy (TON) refers to a pathological condition caused by a direct or indirect insult to the optic nerves, which often leads to a partial or permanent vision deficit due to the massive loss of retinal ganglion cells (RGCs) and their axonal fibers. Retinal microglia are immune-competent cells residing in the retina. In rodent models of optic nerve crush (ONC) injury, resident retinal microglia gradually become activated, form end-to-end alignments in the vicinity of degenerating RGC axons, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(32 citation statements)
references
References 194 publications
(303 reference statements)
0
32
0
Order By: Relevance
“…Therefore, we speculated whether the HMGB1 inhibitor BoxA could inhibit the activation of microglia after ONC. In most cases, ionized calcium-binding adapter molecule 1 (Iba1) can be used to differentiate microglia from other cells [ 13 ]. In the ONC + PBS group, Iba1 (+) cells were mainly distributed in the ganglion cell layer, inner plexiform layer, inner nuclear layer, and outer plexiform layer ( p < 0.05).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, we speculated whether the HMGB1 inhibitor BoxA could inhibit the activation of microglia after ONC. In most cases, ionized calcium-binding adapter molecule 1 (Iba1) can be used to differentiate microglia from other cells [ 13 ]. In the ONC + PBS group, Iba1 (+) cells were mainly distributed in the ganglion cell layer, inner plexiform layer, inner nuclear layer, and outer plexiform layer ( p < 0.05).…”
Section: Resultsmentioning
confidence: 99%
“…Optic nerve crush (ONC) is a well-validated model of TON [ 12 ]. Researchers found that ONC activates retinal microglia and the recruitment of infiltrating macrophages into the retina [ 13 ]. Microglia are the resident immune cells of the central nervous system and the primary initiators of neuroinflammation [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Over the past decades, much effort has been attributed to characterize ramified (resting) and amoeboid (activated) microglia in various neurological disorders that might be an oversimplification. Apart from the classical subdivision of microglia into ramified and amoeboid microglia, bipolar/rod-shaped microglia also appeared in the brains under several pathological conditions ( Ziebell et al, 2012 ; Taylor et al, 2014 ; Au and Ma, 2017 , 2022 ; Bachstetter et al, 2017 ; Edler et al, 2018 ; Holloway et al, 2020 ). In fact, bipolar/rod-shaped microglia was the first form of activated microglia characterized by Nissl in 1899 ( Nissl, 1899 ).…”
Section: Bipolar/rod-shaped Microglia In Alzheimer’s Diseasementioning
confidence: 99%
“…Microglia are morphologically diverse innate immune cells that are originated from primitive myeloid precursors in the embryonic yolk sac ( Ginhoux et al, 2010 ), which account for approximately 5–12% of the total cell population in the mammalian brain ( Dos Santos et al, 2020 ). As an important player for maintaining homeostasis within the CNS throughout the lifetime, microglia are involved in multiple vital cellular processes including immune surveillance, antigen presentation, debris clearance, neuronal apoptosis, maintenance of synaptic activity, and production of cytokine, chemokine and neurotrophic factors ( Tam and Ma, 2014 ; Heneka et al, 2015 ; Ransohoff, 2016a ; Tam et al, 2016 ; Au and Ma, 2017 , 2022 ). Impaired microglial function is often associated with various neurodegenerative diseases such as AD ( Leng and Edison, 2021 ).…”
Section: Microglial Activation and Neuroinflammation In The Aging Brainmentioning
confidence: 99%
“…Moreover, microglia can also promote Wallerian degeneration and axon regeneration. Nevertheless, when microglia and macrophages are depleted, neuron loss is inevitable [121,122]. At the same time, microglia can also produce cytokines, chemokines and ROS, which have neurotoxic effects on RGCs.…”
Section: Inflammatory Mechanisms Involved In the Pathogenic Processmentioning
confidence: 99%